GENETIC VARIATIONS AMONG AQUILARIA SPECIES AND GYRINOPS VERSTEEGII USING AMPLIFIED FRAGMENT LENGTH POLYMORPHISM MARKERS - NURITA TORUAN-MATHIUS; DEWI RAHMAWATI; ANIDAH (BIOTROPIA, 2009)
Aquilaria sp Thymelaeaceae is the most valuable non wood production of  forestry plant in Indonesia It produces a fragrant resin when subjected to fungal attack and has been traded internationally  known  as  gaharu Knowledge  of   genetic  diversity  and  relationship  among species and genus is important for breeding purposes and species conservation In this study genetic variability of  six Aquilaria species were analyzed using the AmplifiedFragment Length Polymorphism  AFLP  markers  Ten  AFLP  primer combinations  amplified  1353  DNA fragments ranging  in size from100 to 350 bp of  which 1285 95 of  them were polymorphic Genetic similarities among Aquilaria sp consisted of  A malaccensis A beccariana A microcarpa and A  crassna  ranged  from 6390  to 7200 based on Dice coefficient The dendrogram derived by the unweighted pair group method with arithmetic mean of  germplasm analysiswere clustered into two main groups Hence a genetic variation among species is quiet high Bootstrap  values for  the  groups  supported  70  of   the  cluster  using  a linear  relationship equation of  r 0724 P 00001 was observedbetween known pedigrees and AFLPderived genetic similarity for 136 pairwise comparisons of  Aquilaria species For example A malacensis and A microcarpa have the highest genetic similarity 7200 compared with another Aquilaria species Primer pairs EACGMCTA produced a specific fragment for A beccariana 850 bp A  crasna 550 bp 180 bp and 140 bp A malaccencis 1500 bp A microcarpa 250 bp and Gyrinops versteegii 150 bp Primer pairs EACGMCAA produced a specific DNA fragment only for A beccariana 1500 bp and 100 bp  Primer pairs EACCMCAC also produced only specific fragment for A crassna 1500 bp Study showed the usefulness of  AFLP analysis in Aquilaria  sp  and  its  potential  application  for  breeding and  species  conservation  Further molecular  diversity  estimated  in  the  present  study  combined  with  the  datasets  on  other morphologicalagronomic  traits will be useful  for  selecting  the appropriate accessions  for plant improvement  through conventional and molecular breeding approaches.Key words Gaharu Aquilaria sp Gyrinops sp genetic diversity molecular marker amplifiedfragment  length polymorphism  AFLP